4x+27=3x+29

Simple and best practice solution for 4x+27=3x+29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+27=3x+29 equation:


Simplifying
4x + 27 = 3x + 29

Reorder the terms:
27 + 4x = 3x + 29

Reorder the terms:
27 + 4x = 29 + 3x

Solving
27 + 4x = 29 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
27 + 4x + -3x = 29 + 3x + -3x

Combine like terms: 4x + -3x = 1x
27 + 1x = 29 + 3x + -3x

Combine like terms: 3x + -3x = 0
27 + 1x = 29 + 0
27 + 1x = 29

Add '-27' to each side of the equation.
27 + -27 + 1x = 29 + -27

Combine like terms: 27 + -27 = 0
0 + 1x = 29 + -27
1x = 29 + -27

Combine like terms: 29 + -27 = 2
1x = 2

Divide each side by '1'.
x = 2

Simplifying
x = 2

See similar equations:

| 1/8x=9/10 | | s=2*pie*r(r+h) | | 2x-3/2=x/4 | | 8/9x1/5 | | 7x-9=9x+2 | | (1/3)x+3=(-2/3)x-5 | | 6x+36=-6x | | 3x-6=22 | | 6+-2*-1.04= | | -2(2s-3)-6=-3(7s+6)-4 | | 3.92=(4x^2)/(0.5-x) | | 7x-51=96 | | g+5.6=10 | | 2/9x7/11 | | k^2-14k+86=0 | | (1/4)(x-3)=-15 | | (6x-1)2=17 | | 4(x+1)^1/2-5(x+1)^3/2+(x+1)^5/2=0 | | (5/8)x=-25 | | 9=2x-10 | | -1y=2x | | W-1.94=5.2 | | 2(x+4)=3(x+9) | | 6+2.3y=3.6 | | k^2-6k+64=0 | | 3x-1=6561 | | 6h-4=5h-4 | | -3+3y=9 | | 4x-20=2y | | 0.20x+0.15(70)=25 | | -5z^2-4z+5=0 | | 2/7x5922 |

Equations solver categories